Comparative Effects of Aerobic Training and Erythropoietin on Oxygen Uptake in Untrained Humans. Issue 8 (August 2016) - Sieljacks, Peter; Thams, Line; Nellemann, Birgitte; Larsen, Mads Sørensen; Vissing, Kristian; Christensen, Britt
Abstract : Abstract: Sieljacks, P, Thams, L, Nellemann, B, Larsen, MS, Vissing, K, and Christensen, B. Comparative effects of aerobic training and erythropoietin on oxygen uptake in untrained humans. J Strength Cond Res 30(8): 2307–2317, 2016—The present study examines responses to 10 weeks of aerobic training and/or erythropoiesis-stimulating agent (ESA) treatment on maximal oxygen uptake (V[Combining Dot Above]O2 max). Thirty-six healthy, untrained men were randomly assigned to sedentary-placebo ( n = 9), sedentary-ESA (SE) ( n = 9), training-placebo (TP) ( n = 10), or training-ESA (TE) ( n = 8). The participants were treated subcutaneously once weekly with ESA (darbepoietin-α, week 1–3; 40 μg and week 4–10; 20 μg) or a placebo for 10 weeks. The training consisted of supervised cycling 3 times per week for 1 hour at an average of 65% of maximal watt, with a progressive overload during the intervention period. V[Combining Dot Above]O2 max, wattmax, and hematological values were measured throughout the study. In addition, the total training workload and estimated energy consumption were recorded after each training session. ESA treatment increased hemoglobin (∼11 and ∼14%, p < 0.001) and hematocrit (∼12 and ∼13%, p < 0.001) in the SE and TE groups, respectively. The relative (but not absolute) increases in V[Combining Dot Above]O2 max were more pronounced ( p < 0.01) in TE (27 ± 6%), compared with SE (15 ± 4%) but not TP (19 ± 4%), indicating that training is superior to ESA in stimulating V[Combining Dot Above]O2 max in untrained men. The increased oxygen uptake in the TE group did not result in higher absolute training workloads than in the TP group. In untrained men, training exhibits a greater stimulus for improvements in V[Combining Dot Above]O2 max than ESA treatment, without pronounced additive effects, which is supported by similar average training workloads and energy consumption in TP and TE. Thus, in untrained men, training alone seems sufficient to induce improvement in V[Combining Dot Above]O2 max.